Probiotic Bacillus Attenuates Oxidative Stress- Induced Intestinal Injury via p38-Mediated Autophagy - Wu, Yanping; Wang, Baikui; Xu, Han; Tang, Li; Li, Yali; Gong, Li; Wang, Yang; Li, Weifen (Frontiers in Microbiology, 2019)
Probiotics have been widely used in maintaining intestinal health and one of their benefits is to enhance host antioxidant capacity. However, the involved molecular mechanisms require further investigated. Autophagy is a self-protection process in response to diverse stresses. We hypothesized that probiotics could modulate intestinal autophagy to alleviate oxidative stress. Sprague-Dawley (SD) rats were orally administered Bacillus SC06 or SC08 daily for 24 days and thereafter received an intraperitoneal injection of diquat (DQ) to induce oxidative stress. We found that rats administered Bacillus SC06 showed better growth performance, more significant intestinal tissue repair and antioxidant properties than those administered SC08, which suggests a strain-specific effect of probiotics. Moreover, SC06 alleviated apoptosis by regulating the expression of Bcl2, Bax and cleaved caspase-3. Further investigations revealed that SC06 triggered autophagy, indicated by the upregulation of LC3 and Beclin1 and the degradation of p62 in rat jejunum and IEC-6 cells. Preincubation with autophagy inhibitor 3-methyladenine (3-MA) significantly aggravated reactive oxygen species (ROS) production and apoptotic cell formation. Furthermore, we demonstrated that p38 MAPK (mitogen-activated protein kinase), not AKT (alpha serine / threonine kinase) / mTOR (mammalian target of rapamycin), was involved in SC06-induced autophagy. Taken together, Bacillus SC06 can alleviate oxidative-induced disorders and apoptosis via p38-mediated autophagy. The above findings highlight a novel mechanism underlying the beneficial effects of probiotics as functional food and provide a new perspective on the prevention and treatment of oxidative damages.